Correlating soil and urban planning for sustainable water cycle - Sharma Sheetal (Journal of Water and Land Development, 2019)
Hydrological modelling and processes using modern hydrological models like SCS Curve Number, HCS, HSPF (Hydrologic Simulation Package-Fortran) and kinematic wave models are widely used nowadays in various researches. But using these modelling in drawing the attention of urban planners for challenges and multiple interactions in heterogeneous urban catchments and water systems is still a shortcoming in water sensitive, planning principle. The art of urban planning and technical implementation using behavioural changes in water responses to urban catchments is the need of present urban planning. The complexities of effects and behavioural changes in the water system or urban catchments and incomplete knowledge of these interactions result in failures of sustainable urban developments. Urban planning needs water sensitive methodology to synchronize soil, water and land cover operational with the population over it. The paper reviews the water sensitive urban planning considering the role of soil in urban planning for water and lands correlations, with the purpose of identifying current limitations and opportunities for future urban planning.